Pengaruh Konten Promosi Instagram terhadap Minat Berorganisasi Mahasiswa - Siti Nahdia Usman; Iman Mauludin; Ilham Akbar Ritonga (Jurnal Ilmu Komunikasi, 2024)
This study aims to examine the influence of Instagram promotional content (@jurnalis_tv) on the organizational interest of Communication and Islamic Broadcasting (KPI) students at UIN Jakarta in the Jurnalis TV community. Additionally, it analyzes the most effective types of content in attracting students to join. The research employs a quantitative approach with a survey method for data collection, involving 32 respondents selected through purposive sampling. Data were analyzed using simple linear regression. The results show that Instagram promotional content has a positive and significant influence on students’ organizational interest, contributing 38.2% to variations in the organizational interest variable. Visual elements and interactive features such as polls and stories proved to be the most effective factors. This research provides recommendations for student organizations to strategically utilize social media to increase appeal and membership.